THE EFFECT OF ATTITUDES, SUBJECTIVE NORMS AND BEHAVIORAL CONTROL ON THE INTERESTS OF SME MANAGERS - Ambardo, Dodod; Riharjo, Ikhsan Budi (International Conference of Business and Social Sciences, 2020)
Entrepreneurship is important for economic development. Entrepreneurship is influenced by how much individual interest, so it is important to know the factors that influence entrepreneurial interest. The purpose of this study was to see the effect of attitudes, subjective norms and behavioral control on the interests of SME managers. This research was conducted on sandals craftsmen entrepreneurs in Wedoro Village, Waru Sidoarjo District. The number of samples used was 75 respondents using a non probability sampling method, with a purposive sampling technique. Data collection using questionnaires. Data analysis techniques used partial least square structural equation modeling (SEM-PLS). The analysis found that attitudes, subjective norms and behavioral control significantly influence the interests of SME.